Dose profile evaluation of a 137Cs source using a solid water phantom - Caio Fernando Teixeira Portela; Thêssa Cristina Alonso; Arnado Prata Mourão (Brazilian Journal of Radiation Sciences)
The precision in the dose values delivered in irradiation processes is essential for the efficiency and quality control of these processes. Radiochromic films can be used to record doses and the calibration of these films must be performed so that they can be used as dosimeters. The planning and control of the radiation released in a process allows to adjust the desired dose in the irradiated object. The photons in the primary beam interact with the matter of the object and the beam energy is attenuated due to these interactions. The attenuation depends on the characteristics of the beam and the composition of the irradiated matter. When a beam of photons propagates on an object, it tends to deposit more energy close to the surface and after reaching the maximum dose value, it decreases the dose values with depth. The films used in this work are of the Gafchromic External Beam Therapy (EBT) type, insensitive to visible light and can be prepared in places where sunlight and artificial light exists. Like many other dosimeters, which follow certain protocols, radiochromic films can provide an absolute dose measurement. Radiochromic films are characterized by their linearity, reproducibility, uniformity, sensitivity, and stability after irradiation. For the realization of the experiments, a part of the film to be irradiated was removed designated as background (BG). BG represents a piece of radiochromic film that will not change and reflects changes in film absorption in relation to environmental conditions such as temperature, visible light and scanning light, for example and that must be handled from it way that the film radiated. In this work, irradiations of a solid water phantom were performed using a source of cesium-137 with the deposition of a maximum absorbed dose value of 2.0 Gy. The phantom was placed 1,0 m far from the source collimator. Radiochromic films were placed inside the phantom to obtain the depth variation dose profile and axial dose profiles measured at 1.0 cm depth in the phantom. The dose variation profile in depth allowed to verify that the maximum dose value happened at a depth between 10 and 13 mm, very close to the surface due to the beam energy range (keV). The axial profiles presented a flatness of about 9.4 cm with a total field of 12 cm in diameter.